Osteoporosis: prevention and treatment - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2010)
The aim of the osteoporosis management is to reduce the risk of fracture. The primary clinical goal is to identify patients at high risk of fracture rather than to identify men or women with osteoporosis. This article summarizes current knowledge about effective prevention and treatment of osteoporosis.